Забезпечення реалізації судом засади доступу до правосуддя стороні захисту - Коровайко, О. І.; Korovaiko, O. I. (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 77-86, 2016)
Проаналізовано питання забезпечення реалізації судом у кримінальному судочинстві України засади доступу до правосуддя стороні захисту. Вказано, що ця засада є складним правовим явищем, у структурі якого слід виділяти організаційні (окремі аспекти функціонування судової системи), процесуальні (створення відповідних процедур, що спрощують доступ осіб до правосуддя) та процесуально-правовий (власне формулювання цього права особи) аспекти, а також систему його гарантій. Для сторони захисту право на доступ до правосуддя є одним з основних засобів забезпечення її прав, свобод та законних інтересів у кримінальному провадженні. Акцентовано увагу, що вказане право тісно пов’язується з низкою інших міжнародних стандартів у сфері кримінального судочинства (право на правову допомогу, розумність строків тощо), а його належне забезпечення судом є дієвим засобом захисту прав та свобод людини й громадянина.

The author has analyzed the issue of guaranteeing the implementation of the access to justice principle for the defense party by the court within the criminal proceedings of Ukraine. It has been indicated that this principle is a complex legal phenomenon, within the structure of which we should outline the organizational (some aspects of the judicial system’s functioning), procedural (creation of the appropriate procedures, simplifying the access to justice for individuals) and procedural and legal (the actual wording of the individual’s right) aspects, as well as the system of its guarantees. The right to access to justice for the defense party is one of the fundamental means of guaranteeing its rights, freedoms and legitimate interests within the criminal proceedings. It has been emphasized that international principles and standards in the sphere of criminal proceedings (in particular the principle of the access to justice) will make it possible to analyze the compliance of the domestic criminal procedural law with generally recognized norms and legal enforcement practices. It has been noted that the institution of the access to justice requires a significant attention by national legislators, especially it concerns the specification and consolidation of the provisions for its content in the relevant norms (the Art. 21 of the Criminal Procedural Code of Ukraine) and taking steps to ensure individual’s procedural rights during criminal proceedings. Special attention is paid to the fact that this right is closely associated with a number of other international standards in the sphere of criminal justice (the right to legal aid, reasonableness of the terms, etc.) and its proper guaranteeing by the court is an effective mean of protecting the rights and freedoms of a man and citizen.

Проанализированы вопросы обеспечения реализации судом в уголовном судопроизводстве Украины основы доступа к правосудию стороне защиты. Указано, что эта основа является сложным правовым явлением, в структуре которого следует выделять организационные (отдельные аспекты функционирования судебной системы), процессуальные (создание соответствующих процедур, упрощающих доступ лиц к правосудию) и процессуально-правовой (собственно формулировка этого права лица) аспекты, а также систему его гарантий. Для стороны защиты право на доступ к правосудию является одним из основных средств обеспечения её прав, свобод и законных интересов в уголовном производстве. Акцентировано внимание на том, что указанное право тесно связано с рядом других международных стандартов в сфере уголовного судопроизводства (право на правовую помощь, разумность сроков и т.п.), а его надлежащее обеспечение судом является действенным средством защиты прав и свобод человека и гражданина.
Guaranteeing the implementation of the access to justice principles for the defense party by the court
Обеспечение реализации судом принципа доступа к правосудию стороне защиты
Коровайко, О. І. Забезпечення реалізації судом засади доступу до правосуддя стороні захисту / О. І. Коровайко // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 4 (75). - С. 77-86.
Коровайко О. І. "Забезпечення реалізації судом засади доступу до правосуддя стороні захисту." Вісник Харківського національного університету внутрішніх справ 4 (2016): 77-86.
Korovaiko, O.I. (2016), “Guaranteeing the implementation of the access to justice principles for the defense party by the court” [Zabezpechennia realizatsii sudom zasady dostupu do pravosuddia storoni zakhystu], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 4, pp. 77–86.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; суд; правосуддя; засади кримінального провадження; доступ до правосуддя; сторона захисту; забезпечення прав учасників кримінального провадження; court; justice; principles of criminal proceedings; access to justice; defense party; guaranteeing the rights ofthe participants in criminal proceedings; правосудие; принципы уголовного производства; доступ к правосудию; сторона защиты; обеспечения прав участников уголовного производства